Standardization of Moringa oleifera leaf powder extracts from different leaf stalk colors as raw material for herbal pharmaceuticals - Fidyasari, Ambar; Estiasih, Teti; Wulan, Siti Narsito; Khatib, Alfi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Standardization in the pharmaceutical field is essential to ensure quality, and to meet chemical, biological, and pharmaceutical standards, including stability assurance as a pharmaceutical product. Specific and non-specific standardizations are conducted to guarantee the efficacy and quality of extracts, which ultimately ensure the pharmacological effects of the plant. This study aims to determine the specific and non-specific standardization parameters of ethanol extracts from green, white, and red Moringa oleifera leaf powder (MOLP). The highest extract yield was obtained from the red-stalked MOLP. The organoleptic analysis of the Moringa leaf extracts from various varieties resulted in thick extracts with a greenish-brown color, characteristic odor, and bitter taste. In the specific parameters, the water-soluble and ethanol-soluble extract contents met the standard of ≥ 5.0%. The non-specific parameters, including loss on drying, total ash content, acid-insoluble ash content, and extract specific gravity, all met the required standards. The total microbial contamination in the extracts met the criteria, remaining below the maximum limit of 10 colonies per gram. The chromatographic profile of the MOLP ethanol extracts obtained by Gas Chromatography-Mass Spectrometry (GC-MS) revealed the presence of terpenoids and steroids. The ethanol extract of MOLP complied with the content standards set by the Indonesian Pharmacopoeia.